Pengembangan Produk Gel Sabun Wajah Ekstrak Buah Belimbing Wuluh (Averrhoa bilimbi L.) dan Daun Sosor Bebek (Kalanchoe pinnata (Lam.) Per.) sebagai Anti Bakteri Penyebab Jerawat - ANARISA BUDIATI; ANNY VICTOR PURBA; SHIRLY KUMALA (Fakultas Farmasi Universitas Pancasila, 2017)
Averrhoa bilimbi L. fruits and Kalanchoe pinnata (Lam.) Per. leaves are useful as anti bacterial. The extracts containing the compound bufadienolides have the potential to be used as an anti bacterial. The purpose of this study to fi nd the best formula of the preparation facial wash gel with the active substance from the combination of extracts. Search methods extract concentration using the agar diff usion to obtain regional Diameter Inhibition (DDH) of each extract and the combinations. Research conducted with 3 forrmula containing extracts with diff erent concentrations. The results of the evaluation of the preparation at room temperature storage does not change the color, shape and scent. Retrieved best formula is the formula I containing a concentration of 0.7% resulting extract preparations light green and scented perfume. The results of the evaluation of the formula I at room temperature after 3 month storage include: high foam in hard water 17 mL, high foam in distilled water >25 mL, the specifi c gravity 1.0386 g/cm3, surface tension 19, 3627 dyne/cm, viscosity 853,33-1103,33 cPs, pseudoplastis fl ow properties, pH 5.16, anti bacterial test results using Diameter test Inhibitory Region shows constraints on Staphylococcus aureus by 5,0±0 mm.